Clinical Radiobiology of Fast Neutron Therapy: What Was Learnt? - Jones, Bleddyn (Frontiers in Oncology, 2020)
Neutron therapy developed from neutron radiobiology, although authorities such as Hal Gray were skeptical about clinical applications for good reasons, despite the higher cell kill per unit dose and the accompanying reduction in oxygen dependency. Gray knew that the increase in RBE with dose fall off could produce marked clinical limitations. After many years of research, this treatment did not produce the expected gains in tumour control relative to normal tissue toxicity as predicted by Gray. The more detailed reasons for this are discussed. Neutrons do not have Bragg peaks and so did not selectively spare many tissues from radiation exposure; the constant neutron RBE tumour prescription values did not represent the probable higher RBE values in late reacting tissues with low α/β values; the inevitable increase in RBE as dose falls along a beam would also contribute to greater toxicity than in a similar megavoltage photon beam. Some tissues such as the CNS white matter had the highest RBEs partly due to their chemical composition, being hydrogen rich. All the above factors contributed to disappointing clinical results found in a series of randomized control studies at many treatment centres, although at the time they were performed neutron therapy was in a catch-up phase with photon based treatments. Their findings are summarized along with their technical aspects and fractionation choices. Better understanding of fast neutron experiments and therapy has been gained through relatively simple mathematical models – using the biological effective dose (BED) concept and incorporating the RBEmax and RBEmin parameters. The RBE itself can then vary between these limits according to the dose per fraction used. These approaches provide useful insights into the problems that can occur in proton and ion beam therapy and how they may be optimised. This is because neutron ionizations in living tissues are mainly caused by recoil protons of an energy proportional to the neutron energy: these are close to the proton energies that occur close to the Bragg peak region. To some extent neutron RBE studies represent the worst case scenario found within proton or ion beams near to Bragg peaks.